Research on the weeds control in maize crop - Alina Simon; Marius Bărdaṣ; Alin Popa (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
The purpose of this paper is to evaluate the degree of dicotyledonous weed species of maize culture, the effectiveness of weed control products and the evaluation of maize yield. Experimental factors A-treatment variants: a1-pre-emergence herbicide with Tender 1.5 l/ha + Merlin Flex 0.4 l/ha (control); a2- pre-emergence herbicide with Tender 1.5 l/ha + Merlin Flex 0.4 l/ha and post-emergence with Titus Plus 300 g/ha; a3- pre-emergence herbicide with Tender 1.5 l / ha + Merlin Flex 0.4 l/ha and post-emergence with Arigo 320 g/ha; a4- pre-emergence herbicide with Tender 1.5 l/ha + Merlin Flex 0.4 l/ha and post-emergence with Principal Plus 420 g/ha; factor B - climatic conditions in the experimental years: b1-2016; b2-2017; b3-2018. In order to achieve the objectives during the period 2016-2018, determinations were carried out regarding the natural enrichment of maize crops by numerical determination of weed species before herbicide and after herbicide treatment at 14, 21 and 28 days, but also before harvesting the crop of maize when carried out and gravimetric determination of the weeds by drying at the oven. Following the determinations made during the growing period of the maize crop, the treatment variant applied to the herbicides Tender 1.5 l/ha + Merlin Flex 0.4 l/ha in pre-emergence and the herbicide Titus Plus 300 g/ha in post-emergence had the best result in combating the weed species existing at the time of the treatment but also the degree of weed reinfestation of the maize crop. Regarding the yield of grain maize determined in the four variants, the highest grain yield (over 6901 kg/ha) was obtained in the fourth treatment variant, with a very significant yiled difference compared to the control variant at which only pre- emergence herbicide was performed.
Keywords: Q01; Q15; Q16; 330; maize; weed control; yield; climatic conditions